Juridical Analysis of Legal Gaps in The Istitha'ah Health Policy Post- Tragedy of 418 Hajj Pilgrims in 2025 - Tohaji, Jihan Tasya Edenia; Roikhan, Muhammad Abdillah (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 3 (2025): Proceeding Annual Symposium on Hajj and Umrah MedicineDO - 10.18860/anshar.v3i0.3788, 2026)
The 2025 Hajj pilgrimage witnessed a tragic paradox marked by a high mortality rate among Indonesian pilgrims, reaching 418 deaths, despite the implementation of stricter health istitha'ah (ability) standards through the Minister of Health Decree No. HK.01.07/Menkes/508/2024. This study conducts a juridical-normative analysis to identify the causes of this failure. Using a pure normative legal research method, the research compares the de jure legal framework (Law No. 8/2019, PP No. 8/2022, Kepmenkes 508/2024) with the de facto situation, including official findings by the DPR RI Timwas. The analysis concludes that the catastrophe was not due to weak substantive norms, but rather a massive implementation failure enabled by fundamental legal gaps in the Legal Structure. These gaps are identified as: (1) an Accountability Gap, due to the absence of explicit sanction clauses; (2) a Coordination Gap, characterized by a vertical normative vacuum in PP No. 8/2022, which fails to grant imperative-binding veto power to the Ministry of Health over the Ministry of Religion's administrative process; and (3) a Hierarchy Gap, concerning the use of a juridically weak instrument (KMK) to restrict fundamental rights. This structural failure creates profound Legal Uncertainty, violating the constitutional right under UUD 1945 Art. 28D(1). The state's failure to provide a legally certain regulation constitutes an omission that opens the door for Onrechtmatige Overheidsdaad claims. Recommendations focus on: adding a sanctions chapter to Law No. 8/2019, elevating eliminative criteria to the PP level, and transforming the screening from a single-point filter to a longitudinal periodic monitoring system.